Anterograde transport blockade precedes deficits in retrograde transport in the visual projection of the DBA/2J mouse model of glaucoma - Dengler-Crish, Christine M.; Smith, Matthew A.; Inman, Denise M.; Wilson, Gina N.; Young, Jesse W.; Crish, Samuel D. (Frontiers in Neuroscience, 2014)
Axonal transport deficits have been reported as an early pathology in several neurodegenerative disorders, including glaucoma. However, the progression and mechanisms of these deficits are poorly understood. Previous work suggests that anterograde transport is affected earlier and to a larger degree than retrograde transport, yet this has never been examined directly in vivo. Using combined anterograde and retrograde tract tracing methods, we examined the time-course of anterograde and retrograde transport deficits in the retinofugal projection in pre-glaucomatous (3 month-old) and glaucomatous (9-13 month old) DBA/2J mice. DBA/2J-Gpnmb+ mice were used as a control strain and were shown to have similar retinal ganglion cell densities as C57BL/6J control mice—a strain commonly investigated in the field of vision research. Using cholera toxin-B injections into the eye and FluoroGold injections into the superior colliculus (SC), we were able to measure anterograde and retrograde transport in the primary visual projection. In DBA/2J, anterograde transport from the retina to superior colliculus (SC) was decreased by 69% in the 9-10 month-old age group, while retrograde transport was only reduced by 23% from levels seen in pre-glaucomatous mice. Despite this minor reduction, retrograde transport remained largely intact in these glaucomatous age groups until 13-months of age. These findings indicate that axonal transport deficits occur in semi-functional axons that are still connected to their brain targets. Structural persistence as determined by presence of estrogen-related receptor beta label in the superficial SC was maintained beyond time-points where reductions in retrograde transport occurred, also supporting that transport deficits may be due to physiological or functional abnormalities as opposed to overt structural loss.